THE ROLE OF PARENTS IN HELPING ONLINE LEARNING DURING COVID-19 IN CLASS III STUDENTS OF SDN 014 SAMARINDA ULU STUDY YEAR 2020/2021 - Yudo Dwiyono; Rarasati Harnowo; Ahmad Ridani (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study aims to: (1) Describe the role of parents in helping children's online learning at home, (2) Determine the supporting and inhibiting factors for online learning during the COVID 19 period. The study was conducted at SDN 014 Samarinda Ulu for two months. The research method used is descriptive qualitative. Data collection techniques using interviews, observation and documentation. The data analysis technique uses the Mile and Huberman model. The results showed that: (1) The role of parents in helping children learn at home online during covid-19 is quite good. Of the subjects studied (parents): (a) There are those who act as parents and as teachers at home in helping children learn online; (b) There are those who advise children to be more active in studying; (c) Some are less involved because they do not understand online learning. (2) Supporting factors for online learning are: (a) Participation from parents who act as teachers at home; (b) Supervision from parents to children in learning; (c) The giving of gifts or punishment from parents to their children. Inhibiting factors are: (a) Inadequate facilities; (b) Parents are busy working, so they do not interact with their children; (c) lack of understanding of parents in online learning.